Transcutaneous spinal cord stimulation modulates quiet standing in healthy adults: stimulation site and cognitive style matter - Shamantseva, Natalia; Timofeeva, Olga; Semenova, Varvara; Andreeva, Irina; Moshonkina, Tatiana (Frontiers in Neuroscience, 2024)
The study explored the effects of transcutaneous electrical spinal cord stimulation (tES) on postural control. Subjects were divided into field-dependent (FD) and field-independent (FI) groups according to their cognitive style. FD subjects use an exteroceptive afferent stream for spatial orientation, while FI subjects use an interoceptive stream. In darkness, vertical posture is maintained by head-trunk stabilization in FD subjects and by independent movements of body segments in FI subjects. Previously, we showed that tES at the L1-L2 vertebral level decreased postural stability in FD subjects. Now, stimulation was applied at the T11-T12 vertebral level (midline, above the left or right dorsal roots). Quiet standing was assessed using stabilometry in 18 FD and FI participants. Participants stood on a force platform in soundproof chamber with eyes closed during tES. Midline and left tES significantly improved postural stability by up to 28% in FD participants, while posture did not change significantly in FI participants. Pronounced differences between the effects of T11-T12 and L1-L2 stimulation are associated with selective topographical activation of proximal and distal leg muscles during tES of the lumbar enlargement. This study highlights the importance of considering cognitive style in postural control research.